PENGARUH UKURAN PERUSAHAAN, CORPORATE SOCIAL RESPONSIBILITY DAN BIAYA LINGKUNGAN TERHADAP PROFITABILITAS PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Iman Karyadi; Virgiyuan Regia Wega Ananda (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of company size, Corporate Social Responsibility (CSR), and environmental costs on the profitability of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Mining companies are one of the sectors that contribute significantly to economic growth; however, their operational activities also have an impact on the environment, requiring companies to pay attention to sustainability and social responsibility aspects. This study uses a quantitative approach with secondary data obtained from annual reports and sustainability reports of mining companies listed on the Indonesia Stock Exchange. The sample selection was conducted using a purposive sampling method based on predetermined criteria. Company size is measured using the natural logarithm of total assets, Corporate Social Responsibility (CSR) is measured based on the disclosure of corporate social responsibility activities, environmental costs are measured based on company expenditures related to environmental activities, while profitability is measured using Return on Assets (ROA). The data analysis method used in this study is multiple linear regression analysis to determine the effect of independent variables on the dependent variable. This study is expected to provide information regarding the factors that influence a company's ability to generate profits and serve as a consideration for management, investors, and stakeholders in assessing company performance by considering economic, social, and environmental aspects.